The Perceptions of Individuals with Intellectual Disability toward Workplace Environment and Practices - Adel Alanazi (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: The examination of the literature on the people with intellectual disabilities reveals significant findings on the policies developed in Saudi Arabia to address their needs, changes in the Saudi culture to accommodate people with disabilities, proactive measures taken by the government to guide behaviors at workplace and discrimination by the employers. However, despite substantial study on these aspects associated with disability, the perceptions of adults with disabilities aspiring for jobs is absent.Method: In this respect the aim of this study is to determine the perceptions of 10 people with intellectual disabilities toward workplace environment and practices in Saudi Arabia. The participants were selected through the help of the Ministry of Human Resources and Social Development, Riyadh. Only 3 participants were male, the rest were female aged 20-26 years and suffering from mild disability. The data were collected through in-depth interviews and then analyzed thematically. Findings: The findings indicate that the participants encounter recruitment challenges in terms of skills requirements, lack of trust from employers, perception of inability to function as required, perceptions of low skills, and low salaries. Discussion: There are many reasons that can explain why such occurrences take place in organizations. The literature details that employers usually find it problematic to hire employees with disabilities and would rather pay them even when not working for the fear that people with disabilities might fail the performance test during the interviews.Conclusion: The government and the corporate world should apply these findings in formulating policies geared to improving the well-being of jobseekers with disabilities and employees in the Saudi Arabia.